Seroprevalence of COVID-19 infection in the Emirate of Abu Dhabi, United Arab Emirates: a population-based cross-sectional study. (24th April 2021) - Alsuwaidi, Ahmed R; Al Hosani, Farida I; Al Memari, Shammah; Narchi, Hassib; Abdel Wareth, Laila; Kamal, Hazem; Al Ketbi, Mai; Al Baloushi, Durra; Elfateh, Abubaker; Khudair, Ahmed; Al Mazrouei, Shereena; Al Humaidan, Hiba Saud; et al.
Abstract: Background: The United Arab Emirates (UAE) was the first country in the Middle East to report severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. Serosurveys are essential to understanding the extent of virus transmission. This cross-sectional study aims to assess the seroprevalence of SARS-CoV-2 infection in the Emirate of Abu Dhabi. Methods: Between 19 July and 14 August 2020, 4487 households were selected using a random sample stratified by region and citizenship of the head of household (UAE citizen or non-citizen). A cluster sample of 40 labour camps was selected. Data on socio-demographic characteristics, risk factors and symptoms compatible with coronavirus disease 2019 (COVID-19) were collected. Each participant was first tested by Roche Elecsys ® Anti-SARS-CoV-2 assay, followed, when reactive, by the LIAISON ® SARS-CoV-2 S1/S2 IgG assay. Results: Among 8831 individuals from households, seroprevalence was 10·4% [95% confidence intervals (CIs) 9·5–11·4], with higher seroprevalence in Abu Dhabi and Al Ain regions compared with those in Al Dhafra. In households, we found no sex difference and UAE citizens had lower seroprevalence compared with those of other nationalities. Among 4855 workers residing in labour camps, seroprevalence was 68·6% (95% CI 61·7–74·7), with higher seroprevalence among workers from Southeast Asia. In households, individuals with higher body mass indexes demonstrated higher seroprevalences than individuals with normal weight. Anosmia and ageusia were strongly associated with seropositivity. Conclusions: The majority of household populations in the Emirate of Abu Dhabi remained unexposed to SARS-CoV-2. In labour camps, SARS-CoV-2 transmission was high. Effective public health measures should be maintained.